Four ways to avoid centripetal effects. How political actors escape institutional incentives in divided societies. Issue 8 (16th November 2020) - Bochsler, Daniel
ABSTRACT: For democracy in ethnically divided societies, political moderation is crucial. The centripetalist school recommends that countries should introduce institutions which offer parties and candidates incentives to rally for votes across ethnic lines. This article discusses the conditions of the centripetal effect of institutions, and actors' strategies to dismantle this effect. Political elites might try to escape the pressure to seek inter-ethnic votes by building strategic electoral alliances that circumvent the centripetal effect, by engineering the composition of voters in electoral districts, engineering group identities, or mobilizing new voters. Empirically, this article analyses mayoral elections under the two-round majority vote, in a context where they display quasi-centripetal features: five South-Eastern European towns with ethnically heterogeneous populations, split evenly between two groups. Results show that political elites only exceptionally resort to centripetal strategies as expected by theory. Instead, alternative strategies, circumventing the centripetal effect, are predominant.